2015
DOI: 10.1186/s40200-016-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and type 2 diabetes; is there any association?

Abstract: BackgroundMigraine headache prevalence and triggers in type2 diabetes mellitus (T2DM) were investigated in previous studies but the results are contradictory. Therefore, in this study we examined the prevalence of migraine headache in diabetic patients in comparison with non-diabetic persons and its predisposing factors in 2014.MethodsWe enrolled 147 volunteer patients with T2DM and 150 healthy persons referred to the Yazd Diabetes Research Center and the Central Laboratory of Yazd, respectively, in 2014. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 31 publications
(51 reference statements)
7
24
1
Order By: Relevance
“…Our results agree with Haghighi et al, 9 who compared 147 patients with type 2 diabetes with data from 150 matched subjects from the general population and observed no significant differences in the prevalence of migraine. In Norway, data from the HUNT 2 and HUNT 3 Surveys found no correlation between migraine and type 2 diabetes, however reported an inverse relationship between migraine and type 1 diabetes (OR 0.47; 95%CI 0.26–0.96) related to microvascular alterations in patients with type 1 diabetes causing diabetic neuropathy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with Haghighi et al, 9 who compared 147 patients with type 2 diabetes with data from 150 matched subjects from the general population and observed no significant differences in the prevalence of migraine. In Norway, data from the HUNT 2 and HUNT 3 Surveys found no correlation between migraine and type 2 diabetes, however reported an inverse relationship between migraine and type 1 diabetes (OR 0.47; 95%CI 0.26–0.96) related to microvascular alterations in patients with type 1 diabetes causing diabetic neuropathy.…”
Section: Discussionsupporting
confidence: 92%
“… 18 20 In Spain, the results of national health surveys have shown that the probability of women suffering from migraine is three times higher than for men (adjusted OR 3.08; 95%CI 2.82–3.37). 4 Haghighi et al 9 found that the proportion of diabetic women with migraine was 62.5% compared to only 37.4% among diabetic men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in spite of the fact that the statistical power was much better for type 2 DM than type 1 DM, we could not confirm the results from the prescription-based study regarding type 2 DM. In accordance with our result, no association between migraine and type 2 DM was found in prospective analyses from the large-scale Women's Health Study (n ¼ 38,620 women) performed in the USA (18) and a case-control study (n ¼ 297) from Iran (17).…”
Section: Comparison With Other Studiessupporting
confidence: 91%
“…A simple comparison between migraine associated symptoms, premonitory symptoms in particular, and symptoms of hypoglycaemia [45] show several similarities: for example, dizziness, pale skin, cold hands and feet, binge eating/sugar cravings, yawning, nausea, low blood pressure, shaking, cognitive difficulties, tiredness, fatigue, visual dysfunction and slurred speech. Increased migraine frequency has also been observed during Ramadan [46] and migraine prevalence in type 2 diabetics was shown to proportionally increase with the number of hypoglycaemia attacks [47].…”
Section: Potentially Migraine Relevant Mechanisms Of Ketosismentioning
confidence: 99%